PENGARUH PENGGUNAAN TEKNIK MIND MAPPING TERHADAP KETERAMPILAN MENULIS TEKS CERITA PENDEK SISWA KELAS XI SMA NEGERI 7 PADANG - Irfani Basri, Teta Marlinda, Harris Effendi Thahar, (Universitas Negeri Padang, 2017)
This study has thraee objectives as follows: (1) Describe the skill of writing short story text of class XI students of SMA Negeri 7 Padang before using the mind mapping technique. (2) describe the skills of writing short story text of class XI students of SMA Negeri 7 Padang after using the mind mapping technique (3) describe the influence of mind mapping technique on the skill of writing short story text of class XI students of SMA Negeri 7 Padang.This research type is quantitative research with experiment method. The design of this study used a single subject group. The population in this study is the students of class XI SMA Negeri 7 Padang registered in the year 2016-2017 which amounted to 128 people. The sample of this research is the students of class XI of SMA Negeri 7 Padang determined by using technique with certain consideration (purposive sampling). This research variable is the skill of writing the text short story text before and after using mind mapping technique of class XI students of SMA Negeri 7 Padang.Â Kata kunci: pengaruh, teknik mind mapping, menulis teks cerpen